1971
DOI: 10.1113/jphysiol.1971.sp009415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of splanchnic nerve stimulation on gastric acid secretion and mucosal blood flow in the anaesthetized cat

Abstract: SUMMARY1. Electrical stimulation of the vagus nerves produced a parallel increase in gastric acid secretion and gastric mucosal blood flow.2. Gastric acid secretion and mucosal blood flow, stimulated by pentapeptide infusions or by vagal stimulation, were markedly and equally reduced by electrical stimulation of splanchnic nerve fibres.3. The splanchnic stimulated reduction in acid and mucosal blood flow occurred only when the rise in blood pressure, normally associated with splanchnic stimulation, was prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

1971
1971
1993
1993

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 14 publications
1
26
1
2
Order By: Relevance
“…suggested that splanchnic stimulation at <4 Hz acted via parasympathetic ganglia but at > 8.Hz it also appeared to have a direct effect on muscle. Reed, Sanders & Thorpe (1971) found that splanchnic stimulation reduced the response to vagal stimulation and to intra-arterial acetylcholine. Furness & Costa (1974) have argued that direct effects of sympathetic neurones on intestinal muscle occur only in vitro or at unrealistically high (> 10 Hz) frequencies of electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…suggested that splanchnic stimulation at <4 Hz acted via parasympathetic ganglia but at > 8.Hz it also appeared to have a direct effect on muscle. Reed, Sanders & Thorpe (1971) found that splanchnic stimulation reduced the response to vagal stimulation and to intra-arterial acetylcholine. Furness & Costa (1974) have argued that direct effects of sympathetic neurones on intestinal muscle occur only in vitro or at unrealistically high (> 10 Hz) frequencies of electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported (Reed, Smy, Venables & Harris, 1973) that burimamide injected in the unstimulated anaesthetized cat does not produce gastric acid secretion. However, these results were obtained in the later parts of experiments in which secretion had previously been stimulated by histamine, gastrin or pentagastrin infusion.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, local intraarterial infusion of either hydrogen peroxide, which can form hydroxyl radicals, or a superoxide generating system, induced macroscopically apparent damage in the mucosa, that was attenuated by concurrent administration of catalase or superoxide dismutase, respectively (Esplugues & Whittle, 1989a (Thompson & Vane, 1953;Reed et al, 1971). Other early studies in the dog demonstrated a reduction in gastric blood flow following parenteral administration of adrenaline or noradrenaline, as determined both by a clearance technique and by electromagnetic flowprobes (Cowley & Code, 1970;Zinner et al, 1975).…”
Section: Microvascular Ischaemia and Injurymentioning
confidence: 99%